On Imam Ghazālī's Farḍ ‘Ain and Farḍ Kifāyah: An Epistemological Approach - Sujiat Zubaidi Saleh; Muhammad Taqiyuddin; Rakhmad Agung Hidayatullah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Imam Ghazālī is the main originator of an integrative Islamic epistemology-based classification of knowledge. Where, the formulation begins with the elaboration of Islamic scientific schools, namely: Kalām, Falsafah, Bāṭinī, and Sufism. This article critically describes the epistemological elements in al-Ghazālī's view. This research is library research. This study concludes that Imam Ghazālī through the classification of his knowledge wants to clarify, that even though all these paths are valid and can be harmonized. This is what prompted Imam Ghazāl to prioritize Sūfī epistemology, where sharia, aqdah and morals in Islam are practiced at the level of ihsān as the main way. Thus, the essential elements related to the classification of knowledge are closely related to the four schools plus the flow of fiqh that he has studied since the beginning of his time of studying. More interestingly, this classification of knowledge can prevent Muslims from being disrupted by epistemology in this contemporary era by remaining based on recognized sources of Islamic epistemology